Strategi Eksekusi Pembiayaan sebagai Upaya Penyelesaian Pembiayaan Bermasalah di Bank Syariah - Susiana, Angella Diana Andi (JIOSE: Journal of Indonesian Sharia Economics, 2023)
This research is a qualitative descriptive research that examines financing execution strategies as an effort to resolve problematic financing in Islamic Banks. The results showed that financing execution is one of the important strategies in resolving problematic financing. This strategy is used to complete the financing of debtors who are no longer prospective. The results of this study show that there are five types of forms of financing execution strategies, namely 1). Business liquidation, namely settlement by selling merchandise stocks, production facilities, even business premises, guarantees and others. 2). Refereeing through BASYARNAS, which is an effort to settle or sell financing guarantees through deliberation with the referee (arbitrate) to obtain a decision, and will be registered with the court for implementation. 3). Parate execution, namely the sale/delivery of financing guarantees made by customers voluntarily to the Bank. 4). Collection agent, the process of collecting payment repayment through a third party, whether it is an individual or an institution. 5). Litigation, the process of forcibly taking over collateral through a court suit.